Book Reviews WeberMarianne. Max Weber: A Biography, translated and edited by ZohnHarry (New York: John Wiley & Sons, 1975), 719 pp., $19.95. - Rogers, Rolf E. (Academy of Management Review, 1977)
This article presents a review of the book ?Max Weber: A Biography,? by Marianne Weber, translated and edited by Harry Zohn.